إساءة المعاملة الوالدية كما يدركها الأبناء وعلاقتها بالكذب لدى عينة من الأبناء في المرحلة العمرية (12 - 15) سنة - عبدالمجيد، فايزة يوسف Abdulmajeed, Fayza Yousef; إسكندر، جيهان عزيز وديع; قاعود، نشأت مهدي السيد محمد Qaoud, Nashaat Mahdi Alsayed Mohammed (جامعة عين شمس - كلية الدراسات العليا للطفولة, 2014)
مشكلة وهدف الدراسة: الكشف عن العلاقة بين إساءة المعاملة الوالدية كما يدركها الأبناء والكذب لدي عينة من أطفال المرحلة العمرية من (12 - 15) عام (دراسة مقارنة بين الذكور والإناث) أهمية الدراسة: تكمن أهمية الدراسة الحالية في ندرة الدراسات التي تناولتها منهج البحث: المنهج الارتباطي والمنهج المقارن عينة الدراسة: 300 تلميذ وتلميذه أعمارهم من (12 – 15) سنة أدوات البحث: مقياس اراء الأبناء في معاملة الوالدين (إعداد فايزة يوسف عبد المجيد 1980)، ومقياس الكذب (إعداد الباحثة)، وإستمارة تحديد المستوي الاجتماعي الثقافي للوالدين (إعداد فايزة يوسف عبد المجيد 1980) نتائج الدراسة: يوجد ارتباط دال إحصائي بين درجات عينة الدراسة علي مقياس الكذب ومقياس إساءة المعاملة الوالدية (الأب)، يوجد ارتباط دال إحصائي بين درجات عينة الدراسة علي مقياس الكذب ومقياس إساءة المعاملة الوالدية (الأم). لا توجد فروق ذات دلالة إحصائية بين متوسطات درجات عينة الدراسة (الذكور - الأناث) علي مقياس الكذب لصالح الذكور، لا توجد فروق ذات دلالة إحصائية بين متوسطات درجات عينة الدراسة (الذكور - الأناث) علي مقياس إساءة المعاملة الوالدية (الأب) لا توجد فروق ذات دلالة إحصائية بين متوسطات ذات دلالة إحصائية بين متوسطات درجات عينة الدراسة (الذكور - الأناث) على مقياس إساءة المعاملة الوالدية (الأم) Study Problem: "What is the relationship between lying and parental maltreatment as perceived by children in a sample of children in the age stage (12 - 15) year olds?' Significance: The current study is crystallized in identifying the relationship between parental maltreatment as perceived by children and lying in the age stage (12- 15) year olds and its relation to lying, a comparative study between males and females as the study significance is defined in rate of studies tackle with this topic. Methods The researcher uses the correlative method and the comparative method. Sample 300 Male/ Female students at age (12-15) yrs old. Tools : Scale of children Points of View in Parental treatment (by Faiza youssef Abdel Meged, 1980), Scale of tying (by researcher), and The Parents Social Cultural Level Form treatment (by Faiza youssef Abdel Meged, 1980). Results: There is a significant statistical correlation among study sample average scores on scale of lying and parental maltreatment (mother). There is a significant statistical correlation among study sample average scores on scale of lying and parental maltreatment (father). There are no significant statistical differences among study sample-average scores (males- females) on scale of lying, in favor of males. There are no significant statistical differences among study sample average scores (males- females) on scale of parental maltreatment (father). There are no significant statistical differences among study sample average scores (males- females) on scale of parental maltreatment (mother).
Keywords: المعاملة الوالدية; العلاقات الأسرية; الآباء والأبناء; الكذب